The Influence of Family Environment, Self-Control, and Financial Literacy on Consumptive Behavior - Ananda, Eka Bela; Surjanti, Jun (International Journal of Emerging Research and Review, 2025)
Objective: College students are often faced with unexpected challenges in financial management, which affects the relevance of decision-making due to the inability to exercise self-control and lack of financial literacy that causes detrimental consumptive behavior. This ponders points to look at the impact of the influence of family environment, self-control, and financial literacy on the consumptive behavior of FEB students in East Java. Method: Data came from 114 respondents at the Faculty of Economics and Business in East Java, Indonesia. The examination in this consider used partial least squares (PLS) prediction for comprehensive information investigation.  Results:  The findings indicate that a supportive family environment can influence student consumptive behavior, good self-control plays a crucial role on consumptive behavior, financial literacy also has a notable influence on consumptive behavior, and overall, family environment, self-control, and financial literacy have a significant effect simultaneously on consumptive behavior of FEB students in East Java. Novelty: These findings are expected to provide recommendations for educational institutions, family environments, especially for students about family environments, self-control, and financial literacy to increase awareness of consumptive behavior.